EMPOWERMENT AND INCREASING SELF-AWARENESS OF XEROSTOMIA AS AN ORAL COMPLICATION OF HEAD AND NECK CANCER THERAPY IN CANCER PATIENTS AT THE INDONESIAN CANCER FOUNDATION, EAST JAVA CHAPTER COORDINATOR - Ayuningtyas, Nurina F.; M., Fatma Yasmin; F., Nisa’a Tassya; T., Irene Anastasia; Viany, Adhistya; Widowati, Kharinna; P., Sri Dewanthy; B., Reiska Kumala (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2025)
This community service project aimed to increase the knowledge and awareness of cancer survivors, particularly those with head and neck cancer, regarding oral complications, especially dry mouth or xerostomia, which often result from radiation and chemotherapy. Data indicates that the prevalence of xerostomia is very high in patients undergoing radiation treatment. To address this issue, the project implemented the Self Oral Screening (SOS) method, a self-screening program that includes filling out questionnaires and examining the oral cavity. The activity also trained participants to create a mouthwash using baking soda. The educational session was conducted at the Indonesian Cancer Foundation in Surabaya, attended by 14 cancer patients and their companions. Evaluation was carried out using a pre-test and post-test to measure the increase in participants' knowledge before and after the education. The average pre-test score was 70.0, while the average post-test score increased to 83.57, showing a significant increase in the participants' knowledge level. However, the evaluation data is still being processed for further publication. Overall, this activity successfully improved participants' knowledge, which is expected to enhance their quality of life through better self-care.